Efficiency of the distribution of youth forums in the Rusafa side of the city of Baghdad: Sadr City as a model - drewel, Hanan Hussain (Al-Adab Journal, 2020)
The current research aims to assess efficiency of youth centres' distribution located in a-Rusafa / Baghdad ( Sadr Ciy), the number of these centres in al-Sadr City is 9 that being distributed among the sectors in al-sadr city , The research relied on important standards to study the distribution of these centres and of these standards:1st. The standard that is depended on the number of population in each sector of Sadr city nd Area standard2 The research deals with some problems suffered by these centres , most importantly, is the financial problem (budget deficit) in the budget of youths centresThe research indicates that there is a shortage in a number of youth centres , where the shortage ranges between 30 to more than 40 youth centresThe research has also indicated that the area of forum in respect to attendants is insufficient to practice all youth activities ( Sport, Cultural , Artistic and Scientific)